Peran Kepuasan Kerja Sebagai Mediator Keadilan Organisasi dan Motivasi Kerja Terhadap Kinerja Guru - Niko Sudibjo; Aluysius Songky Ananta (Universitas Muhammadiyah Surakarta, 2021)
Educational institution such as schools rely heavily on the performance of their teachers in implementing educational practices. Therefore, it is very important for educational institution in managing the teachers’ performance. Factors that are thought to affect performance include organizational justice, motivation and job satisfaction. Therefore, this study aims to examine the effect of organizational justice, work motivation, and job satisfaction on perceptions of the performance of 64 teachers in XYZ junior dan senior high school. The research data obtained were analyzed using a quantitative approach with the PLS-SEM method. The research instrument, a questionnaire to measure the impact of four variabels. The results of this study showed that organizational justice, work motivation and job satisfaction have a positive effect on the performance of XYZ Middle and High School teachers. Job satisfaction variabels succeeded in mediating the effect of work motivation on teacher performance, but on the other hand, job satisfaction did not succeed in mediating the effect of organizational justice on teacher performance.